Development of Rainfall-runoff Model Using Tank Model: Problems and Challenges in Province of Aceh, Indonesia - Hairul Basri (Graduate Program of Syiah Kuala University, 2013)
Abtstract - Rainfall-runoff model using tank model founded by Sugawara has been widely used in Asia. Many researchers use the tank model to predict water availability and flooding in a watershed. This paper describes the concept of rainfall-runoff model using tank model, discuss the problems and challenges in using of the model, especially in Province of Aceh, Indonesia and how to improve the outcome of simulation of tank model. Many factors affect the rainfall-runoff phenomena of a wide range of watershed include: soil types, land use types, rainfall, morphometry, geology and geomorphology, caused the tank model usefull only for concerning watershed. It is necessary to adjust some parameters of tank model for other watershed by recalibrating the parameters of the model. Rainfall runoff model using the tank model for a watershed scale is more reasonable focused on each sub-watershed by considering soil types, land use types and rainfall of the concerning watershed. Land use data can be enhanced by using landsat imagery or aerial photographs to support the validation the existing of land use type. Long term of observed discharges and rainfall data should be increased by set up the AWLR (Automatic Water Level Recorder) and rainfall stations for each of sub-watersheds. The reasonable tank model can be resulted not only by calibrating the parameters, but also by considering the observed and simulated infiltration for each soil and land use types of the concerning watershed. Key words: rainfall-runoff model, tank model, infiltration, land use types, soil types, watershed